Hubungan Jenis Kelamin, Tingkat Pendidikan, dan Indeks Massa Tubuh Dengan Kejadian Hipertensi Pada Lansia di Wilayah Kerja PUSKESMAS Gunungsari Lombok Barat - Nabila, Rahma Igta; Herlinawati, Herlinawati; Ariyanto, Suwondo; Ronanarasafa, Ronanarasafa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Hypertension is a non-communicable disease that commonly occurs among the elderly. This condition poses a risk of causing serious complications if left untreated. This study aims to analyze the relationship between gender, education level, and body mass index (BMI) with the incidence of hypertension in the elderly within the working area of Gunungsari Public Health Center, West Lombok Regency. The study employed an analytical observational design with a cross-sectional approach. A total of 108 respondents were selected using cluster random sampling. Data were collected through interviews, blood pressure measurements, as well as weight and height assessments. Data analysis was conducted using the Chi-Square test to examine the relationship between gender, education level, and BMI with the incidence of hypertension in the elderly. The study results revealed a significant relationship between education level and gender with hypertension, while BMI showed no significant relationship. Elderly individuals with low education levels and high BMI were at greater risk of developing hypertension. These findings have important implications for designing hypertension prevention and management programs, particularly for high-risk elderly populations.